Omics Approach to Axonal Dysfunction of Motor Neurons in Amyotrophic Lateral Sclerosis (ALS) - Suzuki, Naoki; Akiyama, Tetsuya; Warita, Hitoshi; Aoki, Masashi (Frontiers in Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is an intractable adult-onset neurodegenerative disease that leads to the loss of upper and lower motor neurons (MNs). The long axons of MNs become damaged during the early stages of ALS. Genetic and pathological analyses of ALS patients have revealed dysfunction in the MN axon homeostasis. However, the molecular pathomechanism for the degeneration of axons in ALS has not been fully elucidated. This review provides an overview of the proposed axonal pathomechanisms in ALS, including those involving the neuronal cytoskeleton, cargo transport within axons, axonal energy supply, clearance of junk protein, neuromuscular junctions (NMJs), and aberrant axonal branching. To improve understanding of the global changes in axons, the review summarizes omics analyses of the axonal compartments of neurons in vitro and in vivo, including a motor nerve organoid approach that utilizes microfluidic devices developed by this research group. The review also discusses the relevance of intra-axonal transcription factors frequently identified in these omics analyses. Local axonal translation and the relationship among these pathomechanisms should be pursued further. The development of novel strategies to analyze axon fractions provides a new approach to establishing a detailed understanding of resilience of long MN and MN pathology in ALS.